1992
DOI: 10.1111/j.1399-0039.1992.tb01920.x
|View full text |Cite
|
Sign up to set email alerts
|

Sequence differences between HLA‐B and TNF distinguish different MHC ancestral haplotypes

Abstract: The HLA-B locus is extremely polymorphic. We have sequenced a region, CL, telomeric of HLA-B that also shows a high degree of allelic variation which we have shown previously by RFLP analysis. The polymorphism can be accounted for by sequence variation in duplicated, reiterated sequence elements called geometric elements. Comparison of the CL1 and CL2 sequences from the 57.1, 8.1, 18.2 and 7.1 ancestral haplotypes revealed that the lengths of the elements vary, both between the duplicated loci within a haploty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…One of these blocks, the beta block, spans about 300 kb [4] and contains the immunologically relevant HLA-B, HLA-Cw, MICA, and MICB genes. Retrospective and prospective studies have shown that matching donors and recipients for non-HLA DNA sequences in the MHC (beta and delta block matching) can result in improved patient survival and less severe acute graft versus host disease (GVHD) [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…One of these blocks, the beta block, spans about 300 kb [4] and contains the immunologically relevant HLA-B, HLA-Cw, MICA, and MICB genes. Retrospective and prospective studies have shown that matching donors and recipients for non-HLA DNA sequences in the MHC (beta and delta block matching) can result in improved patient survival and less severe acute graft versus host disease (GVHD) [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Their likely conservation in human populations has led some authors to define the notion of 'ancestral' haplotypes, preserved for various possible reasons from early human populations. 7,8 However, the choice of an accurate statistical measure of linkage disequilibrium, as well as its biological interpretation, is not straightforward. 9,10 One reason why linkage disequilibrium is often poorly estimated is that it requires an accurate estimation of haplotype frequencies, which is difficult when sample sizes are small.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the application of an IPD metaanalysis would allow for the verification of the results presented in this study, while at the same time haplotypes could be investigated. A strong linkage disequilibrium between HLA-B*35, HLA-C*04:01 and HLA-DRB1*01:01 alleles has been shown to be preserved from early White populations [38,39]. Thus further information is needed to define whether the associations reported to date represent independent alleles or haplotype dependent effects between different populations.…”
Section: Meta-analysesmentioning
confidence: 86%